Sub-10 nm, high density titania nanoforests–gold nanoparticles composite for efficient sunlight-driven photocatalysis. (23rd August 2017) - Tran, Viet V.; Nguyen, Oanh T. T.; Le, Chi H.; Phan, Tuan A.; Hoang, Ban V.; Dao, Thang D.; Nagao, Tadaaki; Hoang, Chung V.
Abstract: We present the photocatalytic activity in the visible frequencies of the forest-like composite materials composed of sub-10 nm, free-standing TiO2 nanowires (NWs) and the plasmonic gold nanoparticles (AuNPs@TiO2 ). We use the methylene blue (MB) as a probe to examine the photocatalytic activity of the AuNPs@TiO2 in the visible frequencies under various excitation conditions. The AuNPs@TiO2 composite exhibits a rate constant of photodegradation of MB molecules about two folds larger than that of the reported composite materials. The numerical calculation suggests that the hot-electron generation via the non-radiative plasmon damping is more impactful than the plasmon-induced near-field enhancement in the photodegradation process.